بعض الخصائص العزلية لمتراكبات بوليمر_ سيراميك البيزوكهربائية (O3)4.Ti0,6.Zr0(Pb_PVC) - محمد, سمارة جاسم (Al-Nahrain Journal of Science, 2018)
In this research. Study some Dielectric properties of polymer - Ceramic composite and the polymer is PVC and piezoelectric Ceramic component is Lead Zirconate Titanate Pb(Zr0.6,Ti0.4)O3. samples composites prepared by solvent cast method With Weight fraction (15%,30%,45%,60%) dielectric constant increases with increase Weight fraction of ceramics Pb(Zr0.6,Ti0.4)O3 with small increase in 15%,30%,Weight fraction and with large increase in 45%,60% Weight fraction. Also the dielectric loss tanδ is increased by the increasing of Weight fraction for ceramic component Pb (Zr0.6,Ti0.4)O3 .